-6(x+1)-4=22

Simple and best practice solution for -6(x+1)-4=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+1)-4=22 equation:



-6(x+1)-4=22
We move all terms to the left:
-6(x+1)-4-(22)=0
We add all the numbers together, and all the variables
-6(x+1)-26=0
We multiply parentheses
-6x-6-26=0
We add all the numbers together, and all the variables
-6x-32=0
We move all terms containing x to the left, all other terms to the right
-6x=32
x=32/-6
x=-5+1/3

See similar equations:

| .n-25.4=-44.8 | | 2=3h−7 | | -(x+5)+3x=17 | | -12=-1/2x+8 | | 72+1.5x=68+2× | | 84=99-c | | -7+4r=-25 | | -14-(-v)-(-10v)+(14v)=17 | | 46=18+d | | -6=(n2)-10 | | 9=–2r+5 | | 2(c-13)=-16 | | 12=2(x-7) | | 2(4x-8)=3(x+3) | | -48+40x=32+8 | | x+1.57=9.97 | | x+2x-3=14 | | 7x+27=4x-3 | | v-3.29=6.7 | | 8(b+1)+4=3(2b-8)–16 | | 1.5(2x-4(=2(4x+2) | | 10=-3x+31 | | 3(x+4)=6(-x-1) | | 10=4+1/2x | | -(x+8)+2x=10 | | 57+5x+96+3x+7=360 | | 2n−35÷5=5 | | 3/4x=24x= | | z/9+8=-63 | | 22-b=13 | | F(x)=500(1.05)^5 | | k/6+3=17 |

Equations solver categories